The relationship between family involvement and academic variables - Marta Camarero-Figuerola; Jorge-Manuel Dueñas; Ana-Inés Renta-Davids (Research in Social Sciences and Technology, 2020)
Family involvement refers to the different activities and actions that families can do to provide support to their offspring in education. In recent years, studies that evaluate the influence of family involvement on education have increased. Therefore, a review of the literature was carried out to examine the scientific evidence on this subject. Specifically, the review focused on adolescence because this is a possibly conflictive time in schooling, in which family-adolescent relationships usually go through large changes. The study results suggest that family participation is a variable that protects against academic failure. This relationship is stronger in vulnerable populations and ethnic minorities.